Signature-Based Model-Independent Searches at the Large Hadron Collider: An Experimental Strategy Aiming at Safeness in a Theory-Dependent Way. - Beauchemin, Pierre-Hugues (Philosophy of Science, 2020)
Signature-based model-independent (SBMI) searches for new physics form an explorative component of High Energy Physics experiments that aims at avoiding biases toward beyond-the-standard-model theories. In order to maximize their chances of meeting their objectives, however, SBMI searches must be guided by theory about the target phenomena. They correspond to strategy-driven experiments as defined by Koray Karaca, in contrast to Friedrich Steinle's conception of explorative experiments. A concept of type II safeness is proposed to explain how the objectives of the experiment introduce theory dependence in the search strategy. Empirical evidence obtained from Large Hadron Collider experiments can therefore not avoid dependence on theory.